Estimation of Optimal Portfolio Return and Risk on the LQ-45 Index for the 2020-2022 Period Using the Capital Asset Pricing Model (CAPM) (Jurnal Matematika, Statistika dan Komputasi, 2023)
Stocks are one of the financial instruments with fluctuating prices that cannot be predicted accurately, so every investor must be able to estimate returns and risks so that investment objectives can be achieved. The purpose of this study is to determine the estimated return and risk of stock investment through the formation of an optimal portfolio and show that the resulting portfolio is capable of increasing the chances of achieving investment objectives. This research uses stocks listed on the LQ-45 Index for the 2020-2022 period, which can form an optimal portfolio. The method used to form an optimal portfolio is the capital asset pricing model (CAPM) method. The results of this study indicate that there are 14 out of 30 issuers that form an optimal portfolio with an expected portfolio return of 0.52% and a portfolio risk level of 0.26%. The results obtained from this method indicate that by forming an optimal portfolio, investors can diversify the risks that will be obtained with a more optimal rate of return when compared to the rate of return generated by each stock.
Keywords: Capital asset pricing model; optimal portfolio; return; risk